Benefiting from the aesthetics of the pop art school in recycling used environmental and artistic materials to produce artistic handicrafts - Abd El-Aziz, Nashwa Mohamed Issam; Salem, Rasha Hassan Hosny; Bosila, Nagwa Kamel Mohamed (Journal of Humanities & Social Sciences, 2023)
The research assumes that it is possible to benefit from the thought of the Pop Art school in producing artistic handicrafts by recycling the spent environmental materials. The consumer is based on the thought of pop art The research problem is centered on the following question: How can artistic artefacts be produced with environmental raw materials that are consumed based on the thought of the pop art school? The study tools were: a questionnaire to evaluate the designs proposed by a number of (8) arbitrators from the specialized faculty members at King Khalid University. The results of the research came to fulfill its hypotheses as follows: The possibility of benefiting from the used environmental and technical materials and recycling them by producing handicrafts Artistic.